FACTORS INFLUENCING EDUCATION DEPARTMENT STUDENTS IN CHOOSING A TEACHER'S CAREER - Tira Nur Fitria (Politeknik Negeri Jakarta, 2023)
This study describes the factors that influence students of the faculty of teaching and education to choose a career as a teacher. This method is qualitative research. The result of the analysis shows that two factors influence students to become a teacher in internal factors and external factors. Internal factors include 1) students’ perception that being a teacher is a noble job, and 2) students’ desire to be a useful person as a teacher. 3) students’ desire to be a teacher after graduation. 4) students’ first career choice is to be a teacher. 5) students promise of being good teachers and role models for students. 6) students’ obligations to understand the courses during lectures. 7) students’ obligations to conduct training before being a teacher (internship). External factors include 1) students’ ability to interact and communicate with children or teenagers. 2) students’ belief that being a teacher offers an attractive income and good working conditions. 3) students’ belief about their better life and career future. 4) students’ interest to be a teacher is based on themselves and does not demand from their parents, family, friends, or their teachers. 5) students’ belief that the social image of a teacher is good and positive in society. 10) students believe that being a teacher will have free time for other jobs, works, or activities with their family and friends. 11) students’ interest to be a teacher after joining an internship because of having teaching experience. 12) students’ desire to be teachers appeared when they are in college. While other factors are: students’ belief that a teacher to dedicate themselves to improving education in Indonesia, contribute their knowledge to the wider community, provide better education, especially to the younger generation, and make a good change in the lives of others.